Comparative analysis of American and Russian political discourse: A discourse analysis study - Kopik, Monika (LingBaW. Linguistics Beyond and Within, 2023)
This article provides an exhaustive analysis of American and Russian political discourse through the examination of the linguistic techniques employed by President Joe Biden and President Putin in their speeches. The aim of this research is to examine the linguistic approaches employed in referencing social and political traditions in the United States and Russia, investigate disparities in linguistic strategies within both political discourses, and assess variations in semantic outcomes. The analysis has been conducted to answer the following research questions: (1) What are the linguistic methods of referring to social and political traditions in America and Russia? (2) Do the linguistic strategies differ depending on the political discourse? (3) Is the semantic output different depending on the political discourse? The findings reveal marked differences between the two discourses, reflecting the social and political discrepancies between the political systems of the United States and Russia.